Examining football players` perceived social support across organizational levels and its links to holistic talent development outcomes in German youth academies - Wachsmuth, S.; Hauser, L.-L.; Gierens, F. C.; Wolf, S. A.; Hermann, H.-D.; Höner, O. (Psychology of Sport and Exercise, 2024)
Sport research highlights the significance of supportive relationships and a psychologically safe environment for promoting desirable talent development outcomes associated with young athletes` performance, wellbeing, and personal development. Against this background, this study aimed to investigate youth football players` perceived availability of different kinds of social support from various stakeholders along the talent pathway in German elite youth academies (1). It further sought to examine the link of such social support perceptions to wellbeing, sport commitment and individual performance satisfaction as relevant development outcomes (2). Finally, the study examined potential mechanism underlying these associations by considering psychological safety as a potential mediator (3). For this purpose, N = 271 youth academy players participating in teams of under-13s, under-15s, and under-17/19s age groups completed a multi-section online survey including the PASS-Q, PsySafety-Check, and WHO-5 as well as subscales of the ASQ (i.e., individual performance satisfaction) and YSCS (i.e., sport commitment). Multivariate analyses indicated significant differences in players` perceptions of social support depending on its kind and provider as well as on players` age group. Further, path models highlighted the importance of emotional and esteem support provided by coaches and management for players` talent development outcomes. However, psychological safety seemed to only play a minor role within those associations, partially mediating the effects of emotional support. Overall, these findings encourage a critical reflection of youth players` social support needs and opportunities to optimally address those within elite youth academies as prominent talent development environments in football.